Plant Disease, Pests and Erosion of Biodiversity - Girot Pignot, Pascal Oliver (2011)
Biodiversity is the variety of life, in all its forms. It provides the foods and medicines used around the world today, the fibre for clothes, many of the materials for shelter and houses, and a plethora of other goods and services such as soil nutrients, clean water, disease and climate buffering, energy and much else, which sustain the livelihoods of millions of rural poor and on which all people are ultimately dependent. As such, biodiversity is a critical element of human security.